Association of Serum Uric Acid with Parkinson Disease (Bangladesh Journal of Neuroscience, 2013)
Background: Several studies have identified that low serum uric acid (UA) is a possible risk factor for Parkinson Disease (PD). The aim of my study was based on evaluation of association of serum uric acid with Parkinson Disease (PD).Objective: To evaluate the association of serum uric acid with Parkinson Disease(PD).Methodology: It was a case control study carried out in the Department of Neurology of Bangabandhu Sheikh Mujib Medical University. A total 50 patients of PD aged 45 years or above were taken as cases; and age and sex matched 50 healthy subjects or patients other than PD were taken as control. Serum UA levels were measured in both groups. Besides, any association was searched between serum UA with age, sex, duration and stage of PD, BMI and dietary habit.Results: The mean serum uric acid level in case group was 4.25±1.00 mg/dl and that of control group was 4.73±1.29 mg/dl. The mean serum uric acid in case group was statistically significant (p=0.038 which was